2023
DOI: 10.1002/cac2.12422
|View full text |Cite
|
Sign up to set email alerts
|

Antitumoral effects of cannabis in Notch1‐mutated T‐cell acute lymphoblastic leukemia

Abstract: R Antitumoral effects of cannabis in Notch1-mutated T-cell acute lymphoblastic leukemiaDear Editor,In T-cell acute lymphoblastic leukemia (T-ALL), an aggressive hematologic cancer with poor clinical outcomes, more than 50% of cases show NOTCH1-driven transformation [1]. The NOTCH1 receptor signaling pathway is activated through a series of proteolytic cleavages, ultimately causing the release of the active intracellular domain (NICD), which translocates to the nucleus where it promotes transcription of target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…However, they were unable to identify the combinations of compounds that were responsible for this increased potency. In previous publications by our group, we showed that different CBD-rich Cannabis extracts, with equal amounts of CBD but varying concentrations of other minor compounds, lead to diverse anticonvulsant effects in a mouse model of epilepsy ( 29 ), and selective antitumoral effects in Notch1-mutated in T-ALL ( 32 ); suggesting the potential therapeutic effects of other compounds in the extracts in addition to CBD.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…However, they were unable to identify the combinations of compounds that were responsible for this increased potency. In previous publications by our group, we showed that different CBD-rich Cannabis extracts, with equal amounts of CBD but varying concentrations of other minor compounds, lead to diverse anticonvulsant effects in a mouse model of epilepsy ( 29 ), and selective antitumoral effects in Notch1-mutated in T-ALL ( 32 ); suggesting the potential therapeutic effects of other compounds in the extracts in addition to CBD.…”
Section: Discussionmentioning
confidence: 88%
“…The CBD-rich extract was more potent than pure CBD or other high-CBD chemovars ( 32 ). This implied a specific combination of metabolites from the plant potentiate the full antitumor effect.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations